Ergonomic Proposal in the Storage Area of a Plastic Industry Company to Reduce Industrial Risks - Moreno Flores, Ximena Patricia (2023)
This research was aimed at identifying ergonomic risks for the warehouse operators in the workstation of a plastics industry company, it also explained the reason for the ailments caused by bad posture and proposed ergonomic design solutions. It is an applied, quasi-experimental, exploratory and descriptive research; with a mixed approach where a Nordic Questionnaire and the REBA methodology were used, as they detect musculoskeletal symptoms prematurely and a posture analysis is performed when carrying out tasks, as well as measurements of lighting and noise. Ailments caused by uncomfortable postures with a high risk rating were found in activities such as order preparation, revision and accommodation, mainly in parts of the body such as the neck, wrists, lower back and hips. As a result, postures that are viable in the warehouse with the use of equipment were proposed, reducing the risk to negligible and medium rating. No risks were found in relation to lighting and noise.